Origin, transfer and distribution of cantharidin-related compounds in the blister beetle Hycleus scabiosae - Nikbakhtzadeh,MR (2012)
Cantharidin provides chemical protection for the coleopteran families Meloidae and Oedemeridae. In the present study, it was observed that cantharidin concentration in Hycleus scabiosae was slightly decreased from mated females (mean = 0.011 mg/mg of dry weight) to males (mean = 0.010 mg/mg) and considerably diminished in relation to virgin females (mean = 0.005 mg/mg). Significant concentrations of palasonin (21.69 ng/mg among virgins and 17.49 ng/mg in mated females) and palasoninimide (14.62 ng/mg in virgins and 9.17 ng/mg in mated females) were found in H. scabiosae. Palasonin, palasoninimide and cantharidinimide content of eggs were measured as 5.61, 7.69 and 7.80 ng/mg respectively. Surprisingly, males showed no trace of cantharidin-related compounds (CRCs); therefore CRCs in H. scabiosae could not be transferred from males to females and based on experiments employing its deuterated form, cantharidin is probably independently synthesized in females from the male nuptial transfer. An inseminated female incorporates about 38.5 ng of cantharidin (0.34% of the maternal content), 196.35 ng of palasonin (91.82% of maternal content) and 269.15 ng of palasoninimide (96.70% maternal content) into each egg mass during oviposition. It seems that eggs of this meloid species exploit a different array of protective chemicals by increasing the ratio of CRCs versus cantharidin. CRCs are less toxic than cantharidin; therefore, such compounds might have been deposited in eggs as a safer substitute for cantharidin to provide effective protection, but does not simultaneously harm the susceptible embryo.